Response of Forage Chicory to Various Herbicides. Issue 1 (16th October 2015) - Pittman, Jeremy J.; Interrante, Sindy M.; Butler, Twain J.
Abstract : Chicory ( Cichorium intybus L.) is a short‐lived perennial warm‐season forb in the Asteraceae family. Although its use is predominantly as a wildlife food plot component in the Unites States, it is widely used in countries such as New Zealand as alternative forage for livestock. There is potential for utilizing chicory in mixtures with perennial pasture species such as tall fescue { Festuca arundinacea Schreb. [syn. Schedonorus arundinaceus (Schreb.) Dumort]} and alfalfa ( Medicago sativa L.). The objectives of these field experiments were to determine the effects of various herbicides on the percent injury and forage yield of (i) established chicory treated in the spring and (ii) newly‐planted chicory treated in autumn. Pendimethalin, imazethapyr, and flumetsulam alone or with 0.5% methylated seed oil (MSO) were safe to apply regardless of season. Bromoxynil and flumioxazin alone or with 2, 4‐DB were most injurious to chicory regardless of season. In all instances, chicory sufficiently recovered from injury and there were no differences in forage yield among herbicide treatments compared to the untreated controls. Even though chicory injury responses to herbicides were no longer apparent at forage harvest, it is recommended that herbicides that are least injurious to chicory that also provide greatest weed control be used to reduce the risk of chicory stand failure.